2004
DOI: 10.1007/s00122-004-1657-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the outcrossing rate of barley landraces and wild barley populations collected from ecologically different regions of Jordan

Abstract: The results of previous studies conducted at the University of Hohenheim and the International Center for Agricultural Research in the Dry Areas (ICARDA) indicated that the yielding ability and stability of barley (Hordeum vulgare L.) could be improved in environments with drought stress by increasing the level of heterozygosity. This would require increasing the outbreeding rate of locally adapted breeding materials. As a first step, we estimated the outcrossing rate of 12 barley landraces (Hordeum vulgare ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 44 publications
5
77
0
1
Order By: Relevance
“…More xeric sites had a higher self-fertilization rate than mesic sites, with average rates of 99.6 and 97.9%, respectively. A recent study of 12 populations in Jordan that employed microsatellitebased estimates of outcrossing rate reported an average selfing rate of 99.7% (Abdel-Ghani et al 2004). Reports of observed heterozygosity based on numerous studies of allelic diversity in wild barley are consistent in suggesting very high rates of self-fertilization (cf.…”
Section: Discussionmentioning
confidence: 96%
“…More xeric sites had a higher self-fertilization rate than mesic sites, with average rates of 99.6 and 97.9%, respectively. A recent study of 12 populations in Jordan that employed microsatellitebased estimates of outcrossing rate reported an average selfing rate of 99.7% (Abdel-Ghani et al 2004). Reports of observed heterozygosity based on numerous studies of allelic diversity in wild barley are consistent in suggesting very high rates of self-fertilization (cf.…”
Section: Discussionmentioning
confidence: 96%
“…Our data suggested that under certain, currently unknown, circumstances, pollen flow may become substantial as evidenced by high observed heterozygosity in the BG population. Other studies have indicated that high annual precipitation and cool temperature during flowering time may enhance outcrossing in wild barley (Brown et al, 1978b;Abdel-Ghani et al, 2004).…”
Section: Discussion Sgs In a Predominant Selfermentioning
confidence: 98%
“…Extensive genotypic analysis of diverse germplasm has revealed that restricted outcrossing (0-1.8%) 43 , combined with low recombination in pericentromeric regions, has resulted in modern germplasm that shows limited regional haplotype diversity 44 . We investigated the frequency and distribution of genome diversity by survey sequencing four diverse barley cultivars ('Bowman', 'Barke', 'Igri' and 'Haruna Nijo') and an H. spontaneum accession (Methods and Supplementary Note 8) to a depth of 5-25-fold coverage, and mapping sequence reads against the barley cultivar 'Morex' gene space.…”
Section: Natural Diversitymentioning
confidence: 99%